Sintesis Teologi Lingkungan: Perbandingan Pemikiran Seyyed Hossein Nasr Dan Joseph Sittler - Afifudin, Ridho; Rully S, Fajar Muammal (Prodi Sosiologi Agama, 2023)
This article discusses environmental theology in Islam and Christianity, namely, the thoughts of Seyyed Hossein Nasr and Joseph Sittler. In Islam, there is a very important concept of khalifah, in which humans are tasked with protecting and maintaining their natural environment. Meanwhile, in Christianity, the concept of nature’s sacredness teaches that the environment is evidence of God's love that must be well preserved. This article focuses on the thought maps of Seyyed Hossein Nasr and Joseph Sittler in the context of environmental conservation and how the relationship between humans, God, and nature is implemented in life. This study used a literature review method. Data collection and analysis were performed based on the data collected from various scientific sources from the two figures. In addition, data were obtained from various sources relevant to the writing theme. In this comparative study, the thoughts of Seyyed Hossein Nasr and Joseph Sittler are compared in terms of the basic concept of thought, views on the relationship between humans, God, and nature, and the implications of thought for environmental action. In the comparison, it was found that both agreed that the environment must be well preserved and that humans must be responsible for the sustainability of the environment. However, there are differences in their views on the relationship between humans, God, and nature, and how environmental actions can be taken. From the analysis and discussion, it can be concluded that the ideas of the two figures converge in the understanding that humans must begin to change their paradigm towards nature. That nature is a manifestation of God's love; even nature is an emanation of God's presence that must be treated and preserved as humans treat themselves. If so, then it is possible for the sustainability of nature to be easily realized. In the future, it will be possible to realize the continuity of a more moral human civilization.